The Relationship between Pillars of the Contract and its Binding Force - Adnan Malkawi, Bashar (Opción)
A philosophical and practical question about the source of the binding force of the contract is raised by Latin jurisprudence trend and some of Arab laws that have influenced by this trend. Since Romans era, trends differed in understanding and answering this question. So trends moved from formalism in contracts to the given promise in canon law. Then, jurisprudence of autonomy of the will emerged where the most recent theory related to it is utility and justice theory by the French jurist Ghestin. In this research, I will present a new understanding based on the relationship between the contract and its binding force.